2001
DOI: 10.1021/ma0101299
|View full text |Cite
|
Sign up to set email alerts
|

Chain Transfer to Polymer in Free-Radical Solution Polymerization of 2-Ethylhexyl Acrylate Studied by NMR Spectroscopy

Abstract: The effects of initial monomer concentration, [M]o, and percent conversion on the extent of chain transfer to polymer in the free-radical solution polymerization of 2-ethylhexyl acrylate (EHA) have been studied. The polymerizations of EHA were carried out in cyclohexane at 70°C using 2,2′-azobis(2-cyanopropane) at 0.1 wt % relative to monomer as the initiator. 13 C NMR spectra of PEHA show that branching resulted from hydrogen abstraction at backbone C-H bonds, with no evidence for chain transfer in the side g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
123
4
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(139 citation statements)
references
References 11 publications
10
123
4
2
Order By: Relevance
“…With aliphatic acrylates, only the type of MCRs as shown in Scheme 1 will play a significant role. 17 MCRs can in principle be generated by three distinctly different inter-or intramolecular reaction pathways. As stated earlier, the transfer products of all three pathways are identical in electronic nature and in their direct chemical neighborhood.…”
Section: Formation Of Mcr and Follow-on Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…With aliphatic acrylates, only the type of MCRs as shown in Scheme 1 will play a significant role. 17 MCRs can in principle be generated by three distinctly different inter-or intramolecular reaction pathways. As stated earlier, the transfer products of all three pathways are identical in electronic nature and in their direct chemical neighborhood.…”
Section: Formation Of Mcr and Follow-on Reactionsmentioning
confidence: 99%
“…From the abundance of quaternary carbons they deduced the branching frequency and concluded that the origin of these branches must be inter-and more notably intramolecular transfer to polymer reactions [17][18][19] giving a late confirmation for the backbiting theory. [8][9][10] Parallel to the investigations into the level of branching in acrylate polymerizations, difficulties in the determination of the propagation rate coefficient, k p , for alkyl acrylates became apparent.…”
Section: Introductionmentioning
confidence: 99%
“…Similar investigations of free-radical processes with a high rate of chain transfer to polymer include the free-radical solution polymerization of butyl acrylate, [18] 2-ethylhexyl acrylate [19] and free-radical and bulk polymerization of vinyl acetate. [20] Termination by combination and disproportionation are included in the model, as well as chain transfer to monomer and solvent.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…[28] Indirect evidence of branching, by the loss of PLP-structure in polymer MMDs, is documented for a wide range of alkyl acrylates [2,[8][9][10][29][30][31][32] as well as AA. [33,34] Application of a 500 Hz laser extends the temperature range over which chain-end propagation may be measured using the PLP-SEC technique; [9] however, the loss of PLP structure in the polymer MMDs at 70-80 8C is still attributed to the effect of backbiting not only for BA, [9] but also for isobornyl acrylate, tert-butyl acrylate and 1-ethoxyethyl acrylate, [35] and a series of carbamate acrylates.…”
Section: Introductionmentioning
confidence: 99%